Environmental impact assessment of tourism development in marine protected areas: a case study of Tioman island marine park - Ahmad Zaini, Azniza; Mohd Noor, Mohd Iqbal; Ahmad, Badli Esham; Amir Mustafa, Amira Mas Ayu (Universiti Teknologi MARA (UiTM), 2023)
The purpose of this study is to assess the impact on tourism activities in Tioman Island Marine Park by using Life Cycle Assessment theory. This assessment is capable of providing new insights into environmental impact and offering benefits to the policy makers in planning and monitoring tourism activities in protected areas. The results of each assessment case indicated that transportation to/from the island, accommodation, snorkeling activities, and waterfall trekking activities leave negative impacts on human health, ecosystem quality and resources. Transportation cases showed the highest impact on the park environment (339.46 Pt). In addition, the impact of accommodation cases was at 111.81 Pt, at about 20.08% of the total impact. The advantages of Life Cycle Assessment method include it offers a rational and comprehensive approach to evaluate the environmental impacts in every stage of a product's system. However, some limitations were also found in the approach. Problems can arise from the decision making in identifying input-output to determining products' life cycle process or system boundary. Future studies are recommended to identify damage assessments on other tourist sub-systems such as caterer, souvenirs and second tier supplier.